Modeling the Effects of Free Trade Agreements between the EU and Canada, USA and Moldova/Georgia/Armenia on the Austrian Economy: Model Simulations for Trade Policy Analysis - Joseph Francois; Olga Pindyuk (FIW - Research Centre International Economics, 2013)
This study examines the economic impact on Austria of three possible new EU free trade agreements: (1) an EU-US agreement; (2) an EU-Canada agreement; and (3) an EUArmenia/Georgia/Moldova agreement. This is done with a computational model of the global economy. The trade agreements are modeled as a mix of preferential tariff reductions and reductions in non-tariff measures that affect both goods and services. The primary impact follows from NTM reduction rather than tariff reductions. Of the three agreements, a potential agreement with the US is by far the most important. This follows from the size of the US economy. The US accounts for roughly one-quarter of extra-EU Austrian exports. Overall, the combined impact of the FTAs studied is positive. Most of the impact follows from investment response. Productivity gains from NTM reduction mean a combination of increased national income, higher wages, and employment, and increased capital stocks for the Austrian economy.
Keywords: C68; F15; F17; 330; Free trade agreements; EU; Canada; USA; CGE modeling